Validation of Units Of Measurement (Alavaikal) In Traditional Cittā Literature and Its Significance In Traditional Diagnostic Methods: An Epistemological View of Aḷavaikaḷ in Cittā Literature - Rajantheran, M. (International Journal of Psychosocial Rehabilitation, 2020)
The antique Cittā system of medicine has survived since age old period in southern part of India because of its firm basic tenets of Indian Philosophy. While the present day scientific community rejects the intellectual elements used by traditional disciplines claiming them as erroneous belief, it has become mandatory to validate the subjective parameters such as “Aḷavaikaḷ” in classical Cittā text through scientific methodology. The term “Aḷavaikaḷ” in Cittā literature can be referred to as Logics or the prime units of measurement used in the ancient times for disease diagnosis and prognosis. It was also known by the terminology “Piramāṇaṅkaḷ” which constitute the first ever tool in the quest for knowledge. In this review all these traditional tools of knowledge have been carefully analysed and has been interpreted on scientific grounds to overlook on this traditional concept of Cittā literature with no scope of any myth or fallacy and aims to unravel the relationship between the philosophy of Aḷavaikaḷ with that of epistemology and Logical reasoning.